Dopamine treatment during acute hypoxia is neuroprotective in the developing sheep brain. (1st March 2016) - Brew, N.; Azhan, A.; den Heijer, I.; Boomgardt, M.; Davies, G.I.; Nitsos, I.; Miller, S.L.; Walker, A.M.; Walker, D.W.; Wong, F.Y.
Highlights: Pre-treatment with dopamine infusion reduces microglia preterm brains subjected to global severe hypoxia–ischemia. Pre-treatment with dopamine infusion reduces apoptosis in preterm brains subjected to global severe hypoxia–ischemia. Pre-treatment with dopamine infusion has a neuroprotective effect in preterm brains subjected to severe hypoxia–ischemia. Dopamine infusion at a clinically relevant dose does not exacerbate hypoxic–ischemic injury in the preterm brain. Abstract: Dopamine is often used to treat hypotension in preterm infants; these infants are at risk of developing brain injury due to impaired autoregulation and cerebral hypoperfusion. However the effects of dopamine on the immature brain under conditions of cerebral hypoxia are not known. We hypothesized that pretreatment with dopamine would protect the immature brain from injury caused by cerebral hypoxia. Preterm fetal sheep were used to determine the effects of intravenous dopamine on hypoxia-induced brain injury. In 16 pregnant sheep at 90 days of gestation (0.6 of term, term = 147 days) catheters were implanted aseptically into the fetal carotid artery and jugular vein; an inflatable occluder was placed loosely around the umbilical cord for later induction of fetal hypoxemia. At 5 days after surgery, dopamine (10 μg/kg/min, n = 7 fetuses) or saline ( n = 9 fetuses) was infused for 74 h. Two hours after commencing the dopamine/saline infusion, we induced umbilical cord occlusion (UCO) for up to 25 min to produce fetal asphyxia. Fetuses were allowed to recover, and brains were collected 72 h later for assessment of neuropathology. Un-operated twin fetuses were used as age-matched non-UCO controls ( n = 8). In UCO + saline fetuses, microglial and apoptotic cell density in the subcortical and periventricular white matter, caudate nucleus and hippocampus was greater than that in age-matched controls; oxidative stress was elevated in the subcortical and periventricular white matter and caudate nucleus compared to that in age-matched controls. In UCO + dopamine fetuses microglial density and oxidative stress in the cerebral white matter and caudate nucleus were not different to that of age-matched controls. Apoptotic cell death was decreased in the cerebral white matter of UCO + dopamine brains, relative to UCO + saline brains. We conclude that pretreatment with dopamine does not exacerbate hypoxia-induced injury in the immature brain and may be neuroprotective because it led to decreased apoptosis, oxidative stress and neuroinflammation in the cerebral white matter and decreased neuroinflammation in the caudate nucleus.